Pancreatico pleural fistula-a rare complication of chronic calcific pancreatitis - Kumbhar, Suhas G.; Karmarkar, Aditi S. (International Journal of Contemporary Pediatrics, 2025)
Chronic pancreatitis is associated with permanent structural changes in pancreas, leading to impairment of exocrine and endocrine function. Recurrent acute pancreatitis in chronic pancreatitis is a common complication in practice. We came across a rare complication of persistent left sided hemorrhagic pleural effusion due to pancreaticopleural fistula. Diagnosis was made by detection of high levels of pleural fluid lipase and amylase levels. An 11-year-old female presented with fever, abdomen pain and persistent left sided hemorrhagic pleural effusion for four months, which ultimately turned out to be acute on chronic calcific pancreatitis with pancreaticopleural fistula which was successfully surgically treated.